High-ductility cement-based composite material and preparation method thereof
By using sea sand to replace microsilica sand and adding styrene acrylate emulsion in high-ductile cement matrix composites, the problems of material shrinkage deformation and low elastic modulus are solved, the mechanical properties and durability of the material are improved, and economic and Environmentally friendly production effect.
Patent Information
- Application Number
- CN202411502833.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-07
AI Technical Summary
When using microsilicon sand as fine aggregate, existing high-ductility cement-based composites have problems of shrinkage deformation and low elastic modulus. At the same time, the production and output of microsilicon sand are limited, resulting in increased production costs and carbon emissions, which limits its Widely used in engineering.
Sea sand is used to replace microsilicon sand as fine aggregate, and styrene acrylate emulsion is added to the cement matrix composite material to fill the pores and microcracks of the cement matrix through the polymer film to enhance the compactness and water permeability of the material.
It improves the mechanical properties, durability and anti-permeability of cement-based composite materials, reduces the porosity of the material, extends the service life of the material, and reduces production costs and carbon emissions.
Smart Images

Figure BDA0005103038590000141 
Figure BDA0005103038590000151
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to a high-ductility cement-based composite material and a preparation method thereof. Background Art
[0002] High ductility cementitious composite (ECC) is a cementitious composite material designed based on micromechanics theory, with cementitious materials, fine aggregates and reinforcing fibers as the main raw materials. It has excellent ductility, unique strain hardening behavior and multiple cracking characteristics. ECC will show strain hardening after the first cracking, and then it can still maintain its bearing capacity when microcracks develop. The width of microcracks is usually less than 200μm, and the strain reaches 3%-5%, which is 300-500 times that of ordinary concrete. Therefore, ECC has broad application prospects in the fields of building reinforcement, self-resetting seismic structures, bridge engineering, hydraulic structures, etc. At present, microsilica sand is usually used as fine aggregate in the preparation of ECC. However, the average particle size of microsilica sand is about 110μm, and the maximum particle size is about 250μm. The extremely small particle size makes the mortar sand ratio in the ECC mix ratio using it as raw material low, which will have a negative impact on the shrinkage deformation and elastic modulus of ECC. In addition, the origin and output of microsilica sand are limited, and the production and transportation process will increase carbon emissions and economic costs. The adverse effects of microsilica sand on ECC performance and production cost, as well as the ecological environment, restrict the widespread application of ECC in engineering. Therefore, using fine aggregates with large resource reserves and easy access to prepare ECC is an important technical means to promote its sustainable production.
[0003] The Chinese patent application with application number CN202310356014.6 discloses an alkali-resistant aggregate reaction marine engineering concrete, preparation method and application, including: 150-200 parts of cement, 250-300 parts of composite mineral admixture, 20-40 parts of rubber powder, 600-700 parts of sea sand, 930-1000 parts of crushed stone, 15-30 parts of high-efficiency water reducer and 240-320 parts of sea water; wherein the composite mineral admixture is a composite of fly ash, granulated blast furnace slag powder and silica fume. The invention uses sea sand instead of microsilica sand as fine aggregate, which saves costs and alleviates the problem of shortage of river sand resources. However, the addition of sea sand will affect the fresh mix performance and hydration reaction of concrete, and then affect its mechanical properties and durability. Therefore, it is urgent to develop a cement-based composite material that uses sea sand as fine aggregate and does not have much impact on the various properties of the material. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a high-ductility cement-based composite material and a preparation method thereof. The cement-based composite material of the present invention has good mechanical properties, durability and anti-permeability.
[0005] The technical solution of the present invention is as follows:
[0006] One of the purposes of the present invention is to provide a high-ductility cement-based composite material, which is composed of the following raw materials in parts by weight: 281-400 parts of cement, 888-914 parts of fly ash, 66-136 parts of recycled concrete powder, 450-490 parts of sea sand, 320-348 parts of water, 24-27 parts of polyvinyl alcohol fiber, 20-30 parts of styrene acrylate emulsion, and 4-6 parts of water reducer.
[0007] Furthermore, the styrene acrylate emulsion is composed of the following raw materials in parts by weight: 10-20 parts of styrene, 2-10 parts of butyl acrylate, 10-30 parts of methyl methacrylate, 0.5-1 part of sodium dodecyl sulfonate, 20-40 parts of water, and 0.1-0.5 parts of ammonium persulfate.
[0008] Furthermore, the preparation process of the styrene acrylate emulsion is:
[0009] S11: mixing styrene, butyl acrylate and methyl methacrylate according to a set ratio to obtain a monomer mixture for standby use;
[0010] S12: 2 / 3 of the monomer mixture is mixed with 2 / 3 of sodium dodecyl sulfate and 2 / 3 of water to obtain a monomer pre-emulsion for later use;
[0011] S13: Under stirring, add the remaining 1 / 3 of the monomer mixture to a mixed solution of the remaining 1 / 3 of sodium dodecyl sulfate and 1 / 3 of water, and add 1 / 3 of ammonium persulfate, heat to 85°C, and after the appearance of blue light, add the monomer pre-emulsion obtained in step S12 and the remaining 2 / 3 of ammonium persulfate, react for 1-2 hours, and cool to room temperature to obtain the styrene acrylate emulsion.
[0012] Furthermore, the cement is silicate cement P·O42.5.
[0013] Furthermore, the fly ash is primary fly ash, the residue of the fly ash passing through a 45 μm square hole sieve is ≤15%, and the water requirement ratio is ≤95%.
[0014] Furthermore, the preparation process of the recycled concrete powder is as follows:
[0015] S11: Removing impurities from waste concrete;
[0016] S12: adding the waste concrete processed in step S11 into a jaw crusher for crushing to obtain recycled fine aggregate with a particle size of less than 4.75 mm;
[0017] S13: adding the recycled fine aggregate obtained in step S12 into a test small mill for grinding, passing through a 50-mesh sieve, grinding again for 15 minutes, passing through a 100-mesh sieve, grinding for 60 minutes, passing through a 200-mesh sieve, and obtaining recycled concrete micro-powder particles;
[0018] S14: Add the recycled concrete powder particles obtained in step S13 into a muffle furnace at 600-800° C. and calcine for 3-5 hours. After cooling to room temperature, add 2-5% Ca(OH)2 to obtain the recycled concrete powder.
[0019] Furthermore, the fineness modulus of the sea sand is 2.3-3.0.
[0020] Furthermore, the polyvinyl alcohol fiber has a length of 12 mm, a diameter of 40 μm, a tensile strength of 1600 MPa, an elastic modulus of 39 GPa, and a dry breaking elongation of 14%-20%.
[0021] Furthermore, the water reducing agent is polycarboxylic acid high-efficiency water reducing agent powder, the water reduction rate is 32%, and the air content is 2.8%.
[0022] A second object of the present invention is to provide a method for preparing a high-ductility cement-based composite material, comprising the following steps:
[0023] S21: adding a water reducing agent accounting for 1 / 4 into water accounting for 1 / 4, stirring evenly to obtain a water reducing agent solution for standby use;
[0024] S22: adding cement, fly ash, recycled concrete powder, sea sand, and a water reducing agent accounting for 3 / 4 into a mixer according to a set ratio, and stirring for 1 minute. The rotation speed of the stirring process is 57-67 r / min for revolution and 135-145 r / min for rotation.
[0025] S23: Reduce the speed to 57-67 r / min, 135-145 r / min, slowly add 3 / 4 of water, stir until the mixture is fluid, and increase the speed to 120-130 r / min, 280-290 r / min, stir for 2 minutes;
[0026] S24: lower the speed to 57-67 r / min, 135-145 r / min, slowly add 1 / 2 of the polyvinyl alcohol fiber, then increase the speed to 120-130 r / min, 280-290 r / min, stir for 2 min, lower the speed again, slowly add the remaining 1 / 2 of the polyvinyl alcohol fiber, increase the speed and stir for 2 min;
[0027] S25: lowering the speed to 57-67 r / min for revolution and 135-145 r / min for rotation, quickly adding the water reducing agent solution obtained in step S21, and then raising the speed to 120-130 r / min for revolution and 280-290 r / min for rotation, stirring for 1 minute, and obtaining the high ductility cement-based composite material.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. A high-ductility cement-based composite material provided by the present invention is modified by adding styrene acrylate emulsion. After the styrene acrylate emulsion is dispersed in the cement-based composite material, as the water evaporates and the cement hardens, the polymer particles in the emulsion will gradually condense and form a continuous polymer film. This polymer film can fill the pores and microcracks in the cement matrix and enhance the bonding force inside the material. The polymer film formed by the styrene acrylate emulsion in the cement matrix can also effectively fill the pores in the cement paste, reduce the porosity of the material, and thus improve the density of the cement-based composite material. The dense structure can effectively prevent the intrusion of harmful substances such as moisture and gas, and improve the durability of the material. By filling the pores and microcracks, the styrene acrylate emulsion can significantly improve the water penetration resistance of the cement-based composite material, reduce the transmission of water inside the material, and thus reduce the material degradation caused by freeze-thaw cycles, carbonization, chloride ion corrosion, etc.
[0030] 2. In the present invention, cement, fly ash, and recycled concrete powder are used to form a cementitious material system, and fly ash is used in large amounts to replace cement, and recycled concrete powder is used in small amounts to replace cement. In terms of performance improvement, the volcanic ash activity of fly ash can be used to further improve the density of high-ductility cement-based composite materials through secondary hydration. The recycled concrete powder contains relatively high active SiO2 and Al2O3, which can also undergo secondary hydration reaction with cement hydration product Ca(OH)2 to generate CSH gel and promote the development of strength. In terms of environmental protection, the composition of the cementitious material system in the present invention can reduce the amount of cement used, thereby reducing carbon emissions in the cement production process. On the other hand, it can absorb fly ash and waste concrete, by-products of coal-fired power plants, and make comprehensive resource utilization.
[0031] 3. In the present invention, sea sand is used to completely replace microsilica sand as fine aggregate. Compared with microsilica sand, the most notable features of sea sand are large particle size and carrying Cl - 、SO4 2- Mg 2+From the design principle of ECC, cracks start from the initial defects generated in the preparation process of composite materials, and its saturated multi-crack cracking characteristics can only be achieved when there are enough large defects. The larger particle size of sea sand can just become the pre-existing defects in the matrix, improving the tensile limit strain and tensile stability. In addition, the larger particle size of sea sand can also effectively solve the problems of large shrinkage and low elastic modulus caused by the preparation of ECC with microsilica sand. The large amount of fly ash in the cementitious material system will lead to slow early hydration and slow early strength development of ECC. The high content of Cl in sea sand - and SO4 2- It can react with C3A in cement clinker to generate Friedel salt and calcium sulfoxide (AFt) respectively. Friedel salt can accelerate the hydration of cement-based materials and is conducive to the development of early strength of materials. AFt is expansive and can fill the internal pores of the material in the early stage of hydration, optimize the pore structure, and promote the early strength of cement-based materials. From the perspective of economic cost, sea sand is widely produced, easy to obtain, and has low production and transportation costs. In addition, sea sand does not need to be desalinated before use, which is conducive to the promotion and application of ECC.
[0032] 4. The present invention adopts a method of adding materials in batches during the preparation of styrene acrylate emulsion, which can make the polymerization reaction proceed gradually and help to form polymer particles with more uniform particle size. The present invention reduces the problems of uneven particle size and incomplete reaction caused by adding too much monomer at one time, and improves the overall quality of the emulsion.
[0033] 5. The present invention provides a method for preparing a high-ductility cement-based composite material. In view of the material characteristics and the limitations of the existing preparation methods, the loss rate of the powder material is reduced by the pre-wetting method, and the dispersion of the fiber is improved by adding the fiber in batches and then adding mixing water. A preparation method for reducing the loss rate of raw materials and improving the uniformity of the mixture is proposed. The preparation method does not require pretreatment of the material, nor does it require the use of other equipment other than the mixer. The process steps are simple and easy to operate. DETAILED DESCRIPTION
[0034] The present invention is further described below in conjunction with preferred embodiments. The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values; for numerical ranges, the endpoint values of each range, the endpoint values of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein; the materials, reagents, etc. used in the following embodiments, unless otherwise specified, can be obtained from commercial channels; the experimental methods in the following embodiments, unless otherwise specified, are all conventional methods.
[0035] Example 1
[0036] The present embodiment provides a high-ductility cement-based composite material, which is composed of the following raw materials in parts by weight: 281 parts of cement, 888 parts of fly ash, 66 parts of recycled concrete powder, 450 parts of sea sand, 320 parts of water, 24 parts of polyvinyl alcohol fiber, 20 parts of styrene acrylate emulsion, and 4 parts of water reducer.
[0037] In this embodiment, the styrene acrylate emulsion is composed of the following raw materials in parts by weight: 15 parts of styrene, 6 parts of butyl acrylate, 20 parts of methyl methacrylate, 0.8 parts of sodium dodecyl sulfonate, 30 parts of water, and 0.3 parts of ammonium persulfate.
[0038] The preparation process of the styrene acrylate emulsion is:
[0039] S11: mixing styrene, butyl acrylate and methyl methacrylate according to a set ratio to obtain a monomer mixture for standby use;
[0040] S12: 2 / 3 of the monomer mixture is mixed with 2 / 3 of sodium dodecyl sulfate and 2 / 3 of water to obtain a monomer pre-emulsion for later use;
[0041] S13: Under stirring, add the remaining 1 / 3 of the monomer mixture to a mixed solution of the remaining 1 / 3 of sodium dodecyl sulfate and 1 / 3 of water, and add 1 / 3 of ammonium persulfate, heat to 85°C, and after the appearance of blue light, add the monomer pre-emulsion obtained in step S12 and the remaining 2 / 3 of ammonium persulfate, react for 1.5 hours, and cool to room temperature to obtain the styrene acrylate emulsion.
[0042] In this embodiment, the cement is silicate cement P·O42.5, the fly ash is first-class fly ash, the fly ash has a sieve residue of ≤15% passing through a 45μm square hole sieve, a water demand ratio of ≤95%, a fineness modulus of 2.5 for the sea sand, a length of 12mm, a diameter of 40μm, a tensile strength of 1600MPa, an elastic modulus of 39GPa, and a dry breaking elongation of 16%, and the water reducer is a polycarboxylic acid high-efficiency water reducer powder, with a water reduction rate of 32% and an air content of 2.8%.
[0043] In this embodiment, the preparation process of the recycled concrete powder is as follows:
[0044] S11: Removing impurities from waste concrete;
[0045] S12: adding the waste concrete processed in step S11 into a jaw crusher for crushing to obtain recycled fine aggregate with a particle size of less than 4.75 mm;
[0046] S13: adding the recycled fine aggregate obtained in step S12 into a test small mill for grinding, passing through a 50-mesh sieve, grinding again for 15 minutes, passing through a 100-mesh sieve, grinding for 60 minutes, passing through a 200-mesh sieve, and obtaining recycled concrete micro-powder particles;
[0047] S14: Add the recycled concrete powder particles obtained in step S13 into a muffle furnace at 700° C. and calcine for 4 hours. After cooling to room temperature, add 3% Ca(OH)2 to obtain the recycled concrete powder.
[0048] This embodiment also provides a method for preparing a high-ductility cement-based composite material, comprising the following steps:
[0049] S21: adding a water reducing agent accounting for 1 / 4 into water accounting for 1 / 4, stirring evenly to obtain a water reducing agent solution for standby use;
[0050] S22: adding cement, fly ash, recycled concrete powder, sea sand, and a water reducing agent accounting for 3 / 4 into a mixer according to a set ratio, and stirring for 1 minute. The rotation speed of the stirring process is 60 r / min for revolution and 140 r / min for rotation.
[0051] S23: lower the speed to 60 r / min and 140 r / min, slowly add 3 / 4 of water, stir until the mixture is fluid, and increase the speed to 125 r / min and 285 r / min, stir for 2 min;
[0052] S24: lower the speed to 60 r / min, 140 r / min, slowly add 1 / 2 of the polyvinyl alcohol fiber, then increase the speed to 125 r / min, 285 r / min, stir for 2 min, lower the speed again, slowly add the remaining 1 / 2 of the polyvinyl alcohol fiber, increase the speed and stir for 2 min;
[0053] S25: lowering the speed to 60 r / min for revolution and 140 r / min for rotation, quickly adding the water reducing agent solution obtained in step S21, and then raising the speed to 125 r / min for revolution and 285 r / min for rotation, stirring for 1 minute, and obtaining the high ductility cement-based composite material.
[0054] Example 2
[0055] The present embodiment provides a high-ductility cement-based composite material, which is composed of the following raw materials in parts by weight: 400 parts of cement, 914 parts of fly ash, 136 parts of recycled concrete powder, 490 parts of sea sand, 348 parts of water, 27 parts of polyvinyl alcohol fiber, 30 parts of styrene acrylate emulsion, and 6 parts of water reducer.
[0056] In this embodiment, the styrene acrylate emulsion is composed of the following raw materials in parts by weight: 10 parts of styrene, 2 parts of butyl acrylate, 10 parts of methyl methacrylate, 0.5 parts of sodium dodecyl sulfate, 20 parts of water, and 0.1 parts of ammonium persulfate.
[0057] The preparation process of the styrene acrylate emulsion is:
[0058] S11: mixing styrene, butyl acrylate and methyl methacrylate according to a set ratio to obtain a monomer mixture for standby use;
[0059] S12: 2 / 3 of the monomer mixture is mixed with 2 / 3 of sodium dodecyl sulfate and 2 / 3 of water to obtain a monomer pre-emulsion for later use;
[0060] S13: Under stirring, add the remaining 1 / 3 of the monomer mixture to a mixed solution of the remaining 1 / 3 of sodium dodecyl sulfate and 1 / 3 of water, and add 1 / 3 of ammonium persulfate, heat to 85°C, and after the appearance of blue light, add the monomer pre-emulsion obtained in step S12 and the remaining 2 / 3 of ammonium persulfate, react for 1 hour, and cool to room temperature to obtain the styrene acrylate emulsion.
[0061] In this embodiment, the cement is silicate cement P·O42.5, the fly ash is first-class fly ash, the fly ash has a sieve residue of ≤15% passing through a 45μm square hole sieve, a water demand ratio of ≤95%, a fineness modulus of the sea sand of 2.3, a length of 12mm, a diameter of 40μm, a tensile strength of 1600MPa, an elastic modulus of 39GPa, and a dry breaking elongation of 14%, and the water reducer is a polycarboxylic acid high-efficiency water reducer powder with a water reduction rate of 32% and an air content of 2.8%.
[0062] In this embodiment, the preparation process of the recycled concrete powder is as follows:
[0063] S11: Removing impurities from waste concrete;
[0064] S12: adding the waste concrete processed in step S11 into a jaw crusher for crushing to obtain recycled fine aggregate with a particle size of less than 4.75 mm;
[0065] S13: adding the recycled fine aggregate obtained in step S12 into a test small mill for grinding, passing through a 50-mesh sieve, grinding again for 15 minutes, passing through a 100-mesh sieve, grinding for 60 minutes, passing through a 200-mesh sieve, and obtaining recycled concrete micro-powder particles;
[0066] S14: Add the recycled concrete powder particles obtained in step S13 into a muffle furnace at 600° C. and calcine for 3 hours. After cooling to room temperature, add 2% Ca(OH)2 to obtain the recycled concrete powder.
[0067] This embodiment also provides a method for preparing a high-ductility cement-based composite material, comprising the following steps:
[0068] S21: adding a water reducing agent accounting for 1 / 4 into water accounting for 1 / 4, stirring evenly to obtain a water reducing agent solution for standby use;
[0069] S22: adding cement, fly ash, recycled concrete powder, sea sand, and a water reducing agent accounting for 3 / 4 into a mixer according to a set ratio, and stirring for 1 minute. The rotation speed of the stirring process is 57 r / min for revolution and 135 r / min for rotation.
[0070] S23: lower the speed to 57 r / min and 135 r / min, slowly add 3 / 4 of water, stir until the mixture is fluid, and increase the speed to 120 r / min and 280 r / min, stir for 2 min;
[0071] S24: lower the speed to 57 r / min, 135 r / min, slowly add 1 / 2 of the polyvinyl alcohol fiber, then increase the speed to 120 r / min, 280 r / min, stir for 2 min, lower the speed again, slowly add the remaining 1 / 2 of the polyvinyl alcohol fiber, increase the speed and stir for 2 min;
[0072] S25: lowering the speed to 57 r / min for revolution and 135 r / min for rotation, quickly adding the water reducing agent solution obtained in step S21, and then raising the speed to 120 r / min for revolution and 280 r / min for rotation, stirring for 1 minute, and obtaining the high ductility cement-based composite material.
[0073] Example 3
[0074] The present embodiment provides a high-ductility cement-based composite material, which is composed of the following raw materials in parts by weight: 300 parts of cement, 900 parts of fly ash, 100 parts of recycled concrete powder, 480 parts of sea sand, 335 parts of water, 25 parts of polyvinyl alcohol fiber, 25 parts of styrene acrylate emulsion, and 5 parts of water reducer.
[0075] In this embodiment, the styrene acrylate emulsion is composed of the following raw materials in parts by weight: 20 parts of styrene, 10 parts of butyl acrylate, 30 parts of methyl methacrylate, 1 part of sodium dodecyl sulfonate, 40 parts of water, and 0.5 parts of ammonium persulfate.
[0076] The preparation process of the styrene acrylate emulsion is:
[0077] S11: mixing styrene, butyl acrylate and methyl methacrylate according to a set ratio to obtain a monomer mixture for standby use;
[0078] S12: 2 / 3 of the monomer mixture is mixed with 2 / 3 of sodium dodecyl sulfate and 2 / 3 of water to obtain a monomer pre-emulsion for later use;
[0079] S13: Under stirring, add the remaining 1 / 3 of the monomer mixture to a mixed solution of the remaining 1 / 3 of sodium dodecyl sulfate and 1 / 3 of water, and add 1 / 3 of ammonium persulfate, heat to 85°C, and after the appearance of blue light, add the monomer pre-emulsion obtained in step S12 and the remaining 2 / 3 of ammonium persulfate, react for 2 hours, and cool to room temperature to obtain the styrene acrylate emulsion.
[0080] In this embodiment, the cement is silicate cement P·O42.5, the fly ash is first-class fly ash, the fly ash has a sieve residue of ≤15% passing through a 45μm square hole sieve, a water demand ratio of ≤95%, a fineness modulus of 3.0 for the sea sand, a length of 12mm, a diameter of 40μm, a tensile strength of 1600MPa, an elastic modulus of 39GPa, and a dry breaking elongation of 20%, and the water reducer is a polycarboxylic acid high-efficiency water reducer powder, with a water reduction rate of 32% and an air content of 2.8%.
[0081] In this embodiment, the preparation process of the recycled concrete powder is as follows:
[0082] S11: Removing impurities from waste concrete;
[0083] S12: adding the waste concrete processed in step S11 into a jaw crusher for crushing to obtain recycled fine aggregate with a particle size of less than 4.75 mm;
[0084] S13: adding the recycled fine aggregate obtained in step S12 into a test small mill for grinding, passing through a 50-mesh sieve, grinding again for 15 minutes, passing through a 100-mesh sieve, grinding for 60 minutes, passing through a 200-mesh sieve, and obtaining recycled concrete micro-powder particles;
[0085] S14: Add the recycled concrete powder particles obtained in step S13 into a muffle furnace at 800° C. and calcine for 5 hours. After cooling to room temperature, add 5% Ca(OH)2 to obtain the recycled concrete powder.
[0086] This embodiment also provides a method for preparing a high-ductility cement-based composite material, comprising the following steps:
[0087] S21: adding a water reducing agent accounting for 1 / 4 into water accounting for 1 / 4, stirring evenly to obtain a water reducing agent solution for standby use;
[0088] S22: adding cement, fly ash, recycled concrete powder, sea sand, and a water reducing agent accounting for 3 / 4 into a mixer according to a set ratio, and stirring for 1 minute. The rotation speed of the stirring process is 67 r / min for revolution and 145 r / min for rotation.
[0089] S23: lower the speed to 67 r / min and 145 r / min, slowly add 3 / 4 of water, stir until the mixture is fluid, and increase the speed to 130 r / min and 290 r / min, stir for 2 min;
[0090] S24: lower the speed to 67 r / min, 145 r / min, slowly add 1 / 2 of the polyvinyl alcohol fiber, then increase the speed to 130 r / min, 290 r / min, stir for 2 min, lower the speed again, slowly add the remaining 1 / 2 of the polyvinyl alcohol fiber, increase the speed and stir for 2 min;
[0091] S25: lowering the speed to 67 r / min for revolution and 145 r / min for rotation, quickly adding the water reducing agent solution obtained in step S21, and then raising the speed to 130 r / min for revolution and 290 r / min for rotation, stirring for 1 minute, and obtaining the high ductility cement-based composite material.
[0092] Comparative Example 1
[0093] The difference from Example 1 is that this comparative example does not contain styrene acrylate emulsion.
[0094] Comparative Example 2
[0095] The difference from Example 1 is that this comparative example does not contain fly ash.
[0096] The high-ductility cement-based composite material of this comparative example is composed of the following raw materials in parts by weight: 1169 parts of cement, 66 parts of recycled concrete powder, 450 parts of sea sand, 320 parts of water, 24 parts of polyvinyl alcohol fiber, 20 parts of styrene acrylate emulsion, and 4 parts of water reducer.
[0097] Comparative Example 3
[0098] The difference from Example 1 is that this comparative example does not contain recycled concrete powder.
[0099] The high-ductility cement-based composite material of this comparative example is composed of the following raw materials in parts by weight: 347 parts of cement, 888 parts of fly ash, 450 parts of sea sand, 320 parts of water, 24 parts of polyvinyl alcohol fiber, 20 parts of styrene acrylate emulsion, and 4 parts of water reducing agent.
[0100] Comparative Example 4
[0101] The difference from Example 1 is that this comparative example uses microsilica sand instead of sea sand.
[0102] The high-ductility cement-based composite material of this comparative example is composed of the following raw materials in parts by weight: 281 parts of cement, 888 parts of fly ash, 66 parts of recycled concrete powder, 450 parts of microsilica sand, 320 parts of water, 24 parts of polyvinyl alcohol fiber, 20 parts of styrene acrylate emulsion, and 4 parts of water reducer.
[0103] Comparative Example 5
[0104] The difference from Example 1 is that the preparation method of the high ductility cement-based composite material in this comparative example comprises the following steps:
[0105] S21: adding cement, fly ash, recycled concrete powder, sea sand and water reducing agent into a mixer according to a set ratio, and stirring for 2 minutes. The rotation speed of the stirring process is 60 r / min for revolution and 140 r / min for rotation;
[0106] S22: lower the speed to 60 r / min and 140 r / min, slowly add water, stir until the mixture is fluid, and increase the speed to 125 r / min and 285 r / min, stir for 2 min;
[0107] S23: lowering the speed to 60 r / min for revolution and 140 r / min for rotation, slowly adding polyvinyl alcohol fibers, and then raising the speed to 125 r / min for revolution and 285 r / min for rotation, stirring for 2 minutes, and obtaining the high-ductility cement-based composite material.
[0108] Implementation effect evaluation
[0109] The following is a specific test of the high ductility cement-based composite materials obtained in Examples 1-3 and Comparative Examples 1-5 to further illustrate the excellent effects achieved by the present invention:
[0110] Compressive and tensile performance tests: Referring to TCECS1212 "Preparation Method of Strain Hardening Cement-based Composite Material Structure Technical Specification", the high ductility cement-based composite materials obtained in Examples 1-3 and Comparative Examples 1-5 were poured into a 100mm×100mm×100mm plastic test mold to make a cubic compressive strength test piece, and poured into a dog-bone test mold with a thickness of 13mm, a deformation measurement area length of 80mm, and a width of 30mm to make a tensile strength test piece. Referring to the curing method of TCECS1212 Strain Hardening Cement-based Composite Material Structure Technical Specification, after the specimen is solidified, it is immediately covered with a plastic film. After standing for 24 hours, number and demold. After demolding, immediately place it in a standard curing room with a temperature of (20±2)℃ and a relative humidity of more than 95% for curing. After curing for 28 days, take it out and test its compressive and tensile properties on a press and a tensile testing machine.
[0111] Average crack spacing and average crack width test: The average crack spacing and average crack width of Examples 1-3 and Comparative Examples 1-5 were determined by referring to the method described in "Mechanical properties and crack width control of hybrid fiber reinforced ductile cement-based composites" published in the Journal of Building Materials. The specimens used were dog-bone specimens used in the tensile performance test.
[0112] The average crack spacing is calculated as follows:
[0113] S a =L0 / N.
[0114] Among them, L0 is the length of the crack area of the specimen parallel to the loading direction. In this experiment, L0 = 80 mm; N is the number of cracks on the specimen surface within the range of L0, which is determined by a crack observation instrument.
[0115] The average crack width is calculated as follows:
[0116] ω a =(ε t -σ t / E t )L0 / N.
[0117] Among them, ε t is the ultimate tensile strain, σ t is the tensile strength, E t is the elastic modulus, which is determined by reading the stress-strain curve obtained from the tensile performance test; L0 is the length of the cracked area of the specimen parallel to the loading direction. In this experiment, L0=80mm; N is the number of cracks on the specimen surface within the range of L0, which is determined by a crack observation instrument.
[0118] The test results are shown in the following table:
[0119] Table 1 Test results statistics
[0120]
[0121]
[0122] It can be seen from the above table that the high-ductility cement-based composite material prepared by the present invention has excellent compressive strength, tensile strength, ductility and durability. The high-ductility cement-based composite material prepared by the method provided by the present invention does not have agglomeration phenomenon and has a certain improvement in performance.
[0123] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A high ductility cement-based composite material, characterized in that: The invention is composed of the following raw materials in parts by weight: 281-400 parts of cement, 888-914 parts of fly ash, 66-136 parts of recycled concrete powder, 450-490 parts of sea sand, 320-348 parts of water, 24-27 parts of polyvinyl alcohol fiber, 20-30 parts of styrene acrylate emulsion and 4-6 parts of water reducing agent.
2. A high ductility cement-based composite material according to claim 1, characterized in that: The styrene acrylate emulsion is composed of the following raw materials in parts by weight: 10-20 parts of styrene, 2-10 parts of butyl acrylate, 10-30 parts of methyl methacrylate, 0.5-1 part of sodium dodecyl sulfonate, 20-40 parts of water, and 0.1-0.5 parts of ammonium persulfate.
3. A high ductility cement-based composite material according to claim 2, characterized in that: The preparation process of the styrene acrylate emulsion is: S11: mixing styrene, butyl acrylate and methyl methacrylate according to a set ratio to obtain a monomer mixture for standby use; S12: 2 / 3 of the monomer mixture is mixed with 2 / 3 of sodium dodecyl sulfate and 2 / 3 of water to obtain a monomer pre-emulsion for later use; S13: Under stirring, add the remaining 1 / 3 of the monomer mixture to a mixed solution of the remaining 1 / 3 of sodium dodecyl sulfate and 1 / 3 of water, and add 1 / 3 of ammonium persulfate, heat to 85°C, and after the appearance of blue light, add the monomer pre-emulsion obtained in step S12 and the remaining 2 / 3 of ammonium persulfate, react for 1-2 hours, and cool to room temperature to obtain the styrene acrylate emulsion.
4. A high ductility cement-based composite material according to claim 1, characterized in that: The cement is silicate cement P·O42.
5.
5. A high ductility cement-based composite material according to claim 1, characterized in that: The fly ash is first-grade fly ash, the residue of the fly ash passing through a 45 μm square hole sieve is ≤15%, and the water requirement ratio is ≤95%.
6. A high ductility cement-based composite material according to claim 1, characterized in that: The preparation process of the recycled concrete powder is as follows: S11: Removing impurities from waste concrete; S12: adding the waste concrete processed in step S11 into a jaw crusher for crushing to obtain recycled fine aggregate with a particle size of less than 4.75 mm; S13: adding the recycled fine aggregate obtained in step S12 into a test small mill for grinding, passing through a 50-mesh sieve, grinding again for 15 minutes, passing through a 100-mesh sieve, grinding for 60 minutes, passing through a 200-mesh sieve, and obtaining recycled concrete micro-powder particles; S14: Add the recycled concrete powder particles obtained in step S13 into a muffle furnace at 600-800° C. and calcine for 3-5 hours. After cooling to room temperature, add 2-5% Ca(OH)2 to obtain the recycled concrete powder.
7. A high ductility cement-based composite material according to claim 1, characterized in that: The fineness modulus of the sea sand is 2.3-3.
0.
8. The high ductility cement-based composite material according to claim 1, characterized in that: The polyvinyl alcohol fiber has a length of 12 mm, a diameter of 40 μm, a tensile strength of 1600 MPa, an elastic modulus of 39 GPa, and a dry breaking elongation of 14%-20%.
9. The high ductility cement-based composite material according to claim 1, characterized in that: The water reducing agent is polycarboxylic acid high-efficiency water reducing agent powder, with a water reduction rate of 32% and an air content of 2.8%.
10. A method for preparing a high-ductility cement-based composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S21: adding a water reducing agent accounting for 1 / 4 into water accounting for 1 / 4, stirring evenly to obtain a water reducing agent solution for standby use; S22: adding cement, fly ash, recycled concrete powder, sea sand, and a water reducing agent accounting for 3 / 4 into a mixer according to a set ratio, and stirring for 1 minute. The rotation speed of the stirring process is 57-67 r / min for revolution and 135-145 r / min for rotation. S23: Reduce the speed to 57-67 r / min, 135-145 r / min, slowly add 3 / 4 of water, stir until the mixture is fluid, and increase the speed to 120-130 r / min, 280-290 r / min, stir for 2 minutes; S24: lower the speed to 57-67 r / min, 135-145 r / min, slowly add 1 / 2 of the polyvinyl alcohol fiber, then increase the speed to 120-130 r / min, 280-290 r / min, stir for 2 min, lower the speed again, slowly add the remaining 1 / 2 of the polyvinyl alcohol fiber, increase the speed and stir for 2 min; S25: lower the speed to 57-67 r / min for revolution and 135-145 r / min for rotation, quickly add the water reducing agent solution obtained in step S21, then increase the speed to 120-130 r / min for revolution and 280-290 r / min for rotation, stir for 1 minute, and obtain the high ductility cement-based composite material.
Citation Information
Patent Citations
Alkali-resistant aggregate reaction marine concrete and preparation method thereof
CN116217187A